Biorefinery Based on Olive Biomass - Castro, Eulogio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Biomass from olives as a raw material for biorefineries Recent advances in chemical composition determination Latest progress in the extraction and characterization of biocompounds Exploitation of by-products such as wastewater, pomace or olive leaves as raw materials for the production of renewable compounds Applications in bioenergy, renewable chemical production or biofuel production